Overexpression of the carbohydrate binding module of strawberry expansin2 in Arabidopsis thaliana modifies plant growth and cell wall metabolism - Nardi, Cristina Fernanda (2015)
Several cell wall enzymes are carbohydrate active enzymes that contain a putative Carbohydrate Binding Module (CBM) in their structures. The main function of these non-catalitic modules is to facilitate the interaction between the enzyme and its substrate. Expansins are non-hydrolytic proteins present in the cell wall, and their structure includes a CBM in the C-terminal that bind to cell wall polymers such as cellulose, hemicelluloses and pectins. We studied the ability of the Expansin2 CBM (CBMFaEXP2) from strawberry (Fragaria x ananassa, Duch) to modify the cell wall of Arabidopsis thaliana. Plants overexpressing CBMFaEXP2 were characterized phenotypically and biochemically. Transgenic plants were taller than wild type, possibly owing to a faster growth of the main stem. Cell walls of CBMFaEXP2-expressing plants were thicker and contained higher amount of pectins. Lower activity of a set of enzymes involved in cell wall degradation (PG, β-Gal, β-Xyl) was found, and the expression of the corresponding genes (AtPG, Atβ-Gal, Atβ-Xyl5) was reduced also. In addition, a decrease in the expression of two A. thaliana Expansin genes (AtEXP5 and AtEXP8) was observed. Transgenic plants were more resistant to Botrytis cinerea infection than wild type, possibly as a consequence of higher cell wall integrity. Our results support the hypothesis that the overexpression of a putative CBM is able to modify plant cell wall structure leading to modulation of wall loosening and plant growth. These findings might offer a tool to controlling physiological processes where cell wall disassembly is relevant, such as fruit softening.